Adherence to behavioural intervention in RCT study by the women experiencing domestic violence and attending ANC in a public hospital in India-an analysis - Meerambika Mahapatro; Sudeshna Roy; Poonam Nayar; Suruchi Panchkaran; Ashwini Jadhav (Elsevier, 2023)
Background: The paper aims to identify the factors for effective implementation and adherence to the behavioural intervention package by women experiencing domestic violence (DV) and attending ANC in a public hospital. Methods: A qualitative study was undertaken with 211 pregnant women experiencing DV and attending antenatal care (ANC) at the LN Hospital, New Delhi. The intervention was given to women recruited under the RCT study. The narratives were analysed under two broad themes, impeding and facilitating factors, with nine sub-themes. Findings: Impeding factors are external factors generated by the structural interaction of the participants, whereas facilitating factors are supplied internally in the trial to eliminate the influence of impeding factors and singulate the factors under study. Our results show that despite the plethora of impeding factors (nine), the overall sum impact of impeding factors falls short of the positive impact of facilitating factors (nine), which were minor adjustments but reinforce participation in the trial and adherence with 97% follow-up rates. Interpretation: Our study findings are expected to reset the treatment protocol, which entails converting impeding factors into facilitating factors for appropriate adherence and compliance and adequate access and utilization of public services. The sensitization of healthcare providers to the impact of the quality of human interaction on the patient and its impact on the uptake of healthcare services and adherence is needed, particularly in the public hospitals of India. Funding: Funds received for the research are from the Indian Council of Medical Research (ICMR), New Delhi, Government of India.